Analyzing the earliest Chinese proto-porcelain: Study on the materials from Liaotianjianshan kiln sites, Dehua County, Fujian Province (China). Issue 17 (1st December 2018) - Yu, Ge; Jin, Zhengyao; Chen, Lifang; Wang, Fen; Wang, Xiaoran; Wu, Xiaotong; Fan, Anchuan; Xia, Qiongxia
Abstract: The Liaotianjianshan kiln dates back to ca. 3700 years ago as a typical kiln used to manufacture proto-porcelain and stamped stoneware. In this paper, 22 ceramic shard samples from Liaotianjianshan kiln sites were selected to be analyzed by XRF, EMPA-WDS and DIL. The results indicated that the two types of samples have similar chemical characteristics in the body and the consistent firing temperature. The element composition of the kiln sites had low iron and calcium content, which was different from the materials from other areas. The samples had high calcium glazes. Two different types of glaze recipes were distinguished by the content of the minor elements, which also corresponded to the changes in the glaze color. The regular change of the glaze composition and the color reflected an advanced ability of the craftsman to control the glaze recipes. The ceramic properties and the technical maturity revealed that the manufacturing technology of the proto-porcelain of the Liaotianjianshan sites were in the leading level in Southern China during Xia and Shang periods, and Quanzhou seems to be one of the original producing locations of proto-porcelain within China.